2002
DOI: 10.1309/vjaa-l52p-fgrm-qgru
|View full text |Cite
|
Sign up to set email alerts
|

Five Fully Automated Methods for Performing Immature Reticulocyte Fraction

Abstract: We performed a parallel evaluation of 5 automated reticulocyte counters to produce the immature reticulocyte fraction (IRF). We analyzed 225 samples from healthy control subjects, 115 from patients with various diseases, 38 with advanced aplasia, and 22 in early erythropoietic recovery after chemotherapy or bone marrow transplantation. The reference intervals were different for each instrument (ADVIA 120, 0.04-0.25; CELL DYN 4000, 0.15-0.35; GEN-S, 0.20-0.37; SE 9500 RET 0.05-0.21; VEGA RETIC: 0.06-0.23). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 12 publications
1
26
0
1
Order By: Relevance
“…We are aware of only one study using the ADVIA system for reticulocyte determinations with results separately reported for normal adult male subjects [25]: such results showed lower reticulocyte number and immaturity than in the subjects of the present study (normal values reported: reticulocyte number: 29-69 x10 3 /L; reticulocyte %RBC: 0.5-1.4; MRF: 1.5-10.7%; HRF: 0-2.0%). Other results of reticulocytes determinations were more similar to those found in this study, but they were in relation to samples including children and ill subjects [26,27], or were obtained with instruments other than the ADVIA system [28].…”
Section: Discussionsupporting
confidence: 84%
“…We are aware of only one study using the ADVIA system for reticulocyte determinations with results separately reported for normal adult male subjects [25]: such results showed lower reticulocyte number and immaturity than in the subjects of the present study (normal values reported: reticulocyte number: 29-69 x10 3 /L; reticulocyte %RBC: 0.5-1.4; MRF: 1.5-10.7%; HRF: 0-2.0%). Other results of reticulocytes determinations were more similar to those found in this study, but they were in relation to samples including children and ill subjects [26,27], or were obtained with instruments other than the ADVIA system [28].…”
Section: Discussionsupporting
confidence: 84%
“…IRF at T 0 and T 1 were significantly different from levels at T baseline with a P ‐value of 0.01 for both comparisons. The median IRF at T baseline was 0.068% and was within the normal reference range (0.015–0.121%) which was established locally using methods as proposed (Buttarello et al 2002). Although IRF at T 0 and T 1 remained within this range, the distribution at T 0 was skewed towards the upper end and T 1 towards the lower end.…”
Section: Resultsmentioning
confidence: 99%
“…Among elite athletes, IRF reference ranges were found not significantly different from a sedentary control population although additional studies have indicated that athletes generally exhibit higher values than the average although never reaching pathological ranges (Banfi & Del Fabbro 2007; Banfi et al 2005; Banfi et al 2006b). IRF has also been shown to be independent of technology used for their assessment when studying populations of athletes despite an evaluation between five fully automated methods for measuring IRF showed that the reference intervals for normal population were different for each of the instrument (Banfi, Corsi & Melegati 2006a; Buttarello et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to standardize the results obtained from different methods, IRF was defined as the sum of the populations of high and medium IRFs for the systems that identify three populations of differing maturity, as does the ADVIA 120 (Buttarello et al, 2002). To our knowledge, no studies have been published evaluating the usefulness of this parameter in dogs; few significant differences between groups in the present study were found and they are difficult to interpret.…”
Section: Discussionmentioning
confidence: 90%